2022
DOI: 10.3390/ijms23042198
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Interleukins in Recurrent Implantation Failure: A Comprehensive Review of the Literature

Abstract: Recurrent implantation failure (RIF) is a multifactorial condition affecting 10–15% of in vitro fertilization (IVF) couples. Data suggest that functional dysregulation of the endometrial immune system constitutes one of the main pathophysiological mechanisms leading to RIF. The aim of this article is to provide a thorough presentation and evaluation of the role of interleukins (ILs) in the pathogenesis of RIF. A comprehensive literature screening was performed summarizing current evidence. During implantation,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 138 publications
(260 reference statements)
0
22
0
Order By: Relevance
“…Recurrent implantation failure (RIF) constitutes one of the most challenging pathologies encountered in the field of human reproduction, raising concerns among researchers and clinicians alike. There is a lack of consensus regarding the exact definition of RIF; nonetheless, the most widely accepted definition refers to RIF as the failure to achieve a clinical pregnancy following at least three or more consecutive transfers of good-quality embryos in fresh or frozen cycles for woman younger than 40 years of age [ 18 ]. Hysteroscopy and the treatment of hydrosalpinxes have been proven to be effective tools for the management of RIF cases [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent implantation failure (RIF) constitutes one of the most challenging pathologies encountered in the field of human reproduction, raising concerns among researchers and clinicians alike. There is a lack of consensus regarding the exact definition of RIF; nonetheless, the most widely accepted definition refers to RIF as the failure to achieve a clinical pregnancy following at least three or more consecutive transfers of good-quality embryos in fresh or frozen cycles for woman younger than 40 years of age [ 18 ]. Hysteroscopy and the treatment of hydrosalpinxes have been proven to be effective tools for the management of RIF cases [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Despite tremendous advances in reproductive medicine, it remains an ongoing conundrum. About 15% of patients seeking IVF treatment are reported to be afflicted by RIF, which is a huge distress and frustration for both patients and clinicians ( 3 ). Statistics have shown that approximately 40% of euploid blastocysts fail to implant in transfers, which suggests the desynchronization between the embryo and the endometrium in the window of implantation (WOI) as a potential cause of RIF ( 4 , 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the majority of these patients do not achieve a successful pregnancy despite the transfer of normally developing highquality embryos. Impaired maternal endometrial receptivity is the key reason for the failure of embryo implantation in these patients [4][5][6]. Endometrial epithelial cells, which are under the control of oestrogen and progesterone, play a key role in the establishment of endometrial receptivity in the mid-secretory phase and mediate the first contact between the blastocyst and the maternal uterus [7].…”
Section: Introductionmentioning
confidence: 99%